Synthesis and biological activity of benzo-fused 7-deazaadenosine analogues. 5- and 6-substituted 4-amino- or 4-alkylpyrimido[4,5-b]indole ribonucleosides - Tichý, Michal; Pohl, Radek; Tloušt'ová, Eva; Weber, Jan; Bahador, Gina; Lee, Yu-Jen; Hocek, Michal (Bioorganic & medicinal chemistry, 2013)
Two series of new 4-aminopyrimido[4,5-b]indole ribonucleosides bearing phenyl or hetaryl group at position 5 or 6 have been prepared by Suzuki or Stille cross-coupling reactions employing X-Phos ligand with (het)arylboronic acids or stannanes. A series of 4-substituted nucleosides has been also prepared by Pd-catalyzed cross-couplings or nucleophilic substitution. Some of these compounds displayed moderate antiviral activities against HCV and dengue viruses.
Keywords: Antiviral Agents; Cell Survival; Palladium; Hepacivirus; lidé; HeLa Cells; Catalysis; Indoles; buňky Hep G2; adenosin; Hep G2 Cells; Dengue Virus; viabilita buněk; HL-60 buňky; ribonukleosidy; katalýza; antivirové látky; HeLa buňky; Humans; Ribonucleosides; nádorové buněčné linie; Adenosine; indoly; palladium; virus dengue; HL-60 Cells; Cell Line, Tumor